Extension Workers as Mediators: Analysis of the Role of Knowledge Transfer in Encouraging Sustainable Rice Farming Practices - Wahyu Ramadani; Megawati Megawati; Fadillah Nurdin; Makmur Makmur (FAKULTAS PERTANIAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2026)
This study aims to analyze the role of agricultural extension workers in increasing rice production in Lappacinrana Village, Bulupoddo District, Sinjai Regency. The background of the study is based on the low local rice productivity, which is influenced by limited technical assistance, extension intensity, and farmers' ability to access modern agricultural information. This study used a quantitative descriptive method involving 72 rice farmer respondents. Data were collected through observation, questionnaires, structured interviews, and documentation, then analyzed using multiple linear regression with the help of SPSS. The results showed that the role of extension workers as guides, technicians, and consultants had a significant effect on increasing rice production, indicated by a significance value of <0.05 for each. Meanwhile, the role of extension workers as a dynamist did not have a significant effect, indicating that the function of mobilizing farmer groups was not yet optimal. Among all variables, the role of extension workers as technicians emerged as the most dominant factor in increasing production results. Simultaneously, all four roles of extension workers were proven to have a significant effect on increasing rice production. These findings suggest that strengthening the technical and consultative capacity of extension workers is an important strategy for increasing farmer productivity and the effectiveness of extension at the village level.